FILM â€œKEHORMATAN DI BALIK KERUDUNGâ€ SEBAGAI LIVING AL-QURAN - Ahmad Muttaqin (UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
The film,â€œKehormatan di Balik Kerudungâ€ (read: KdBK) is a religious Indonesian filmÂ containing gender issues.In relation to this, it is necessary to view this movie as livingAlQuranphenomenon. By using femenism approach, this paper concludes that first, theâ€œKdBKâ€ movieÂ contains gender issue as reception from Q.S. Ali â€˜Imran (3): 132. Second, many gender imbalanceÂ issues are showed from this movienamely, discrimination, stereotype, subordination, marginal issueÂ and double burden.Film,